Peran Akuntansi dalam Membentuk Disiplin dan Tanggung Jawab Financial Remaja SMK IPTEK Tangsel - Syamsuri, Syamsuri; Suharna; Helmi Purba, Sofyan (Abdimisi, 2025)
Students at SMK IPTEK Tangerang Selatan still face limited understanding of the importance of accounting in everyday life. Many of them have not developed consistent financial management habits, tend to spend money impulsively, and are often unaware of the long-term consequences of undisciplined financial behavior. This situation may hinder their readiness to continue their studies or enter the workforce, where independence and financial responsibility are essential competencies. This community service program aims to improve students’ knowledge and skills in applying basic accounting principles while fostering discipline and financial responsibility in managing personal funds. To achieve these goals, the program includes interactive workshops, hands-on practice in daily financial recording, pocket-money management simulations, and group discussions that help students reflect on their financial habits. These methods provide practical experience in preparing simple financial notes and reports, allowing students to understand the real benefits of accounting. The program’s contribution is not only reflected in the development of students’ competencies but also in the creation of a practical learning module that teachers can use for future activities. Through this initiative, the program is expected to cultivate a culture of financial discipline within the school environment and better prepare students to face economic challenges in the future. Keywords: Accounting; Discipline; Responsibility; Financial